Silence of resident microglia in GPI anchorless prion disease and activation of microglia in Gerstmann-Sträussler-Scheinker disease and sporadic Creutzfeldt-Jakob disease. Issue 1 (4th November 2022) - Noguchi, Hideko; Koyama, Sachiko; Yagita, Kaoru; Shijo, Masahiro; Matsuzono, Kosuke; Hamasaki, Hideomi; Kanemaru, Takaaki; Okamoto, Tsuyoshi; Kai, Keita; Aishima, Shinichi; Abe, Koji; Sasagasako, Naokazu; et al.
Abstract: GPI anchorless prion diseases (GPIALPs) show numerous coarse prion protein (PrP) deposits in the CNS but neuropil spongiform changes are mild and the incidence of dementia is low. Here, we examined differences in resident microglial phenotypes between GPIALP (D178fs25) and the other prion diseases Gerstmann-Sträussler-Scheinker (GSS) disease and sporadic Creutzfeldt-Jakob disease (sCJD) with respect to homeostasis and activation. Immunohistochemistry was performed on 2 GPIALP (D178fs25), 4 GSS (P102L), and 4 sCJD cases. Homeostatic microglia expressing TMEM119 and P2RY12 were preserved in GPIALP compared to GSS and sCJD. Microglia/macrophage activation in GSS and sCJD was associated with the extent of spongiform change. Immunoelectron microscopy revealed TMEM119 and P2RY12 in PrP plaque cores. Activated microglia/macrophages expressing HLA-DR and CD68 were predominant in GSS and sCJD whereas in GPIALP, homeostatic microglia were retained and activated microglia/macrophages were rarely observed. These data suggest that PrP deposition in GPIALP is less toxic and that microglia may be immune-tolerant to PrP deposition. This may be associated with milder tissue damage and a low incidence of dementia. Whereas microglia/macrophage activation is considered to be a reaction to tissue injury, this study shows that the degree of microglia/macrophage activity might influence the extent of tissue damage.